Tamansiswa's Spirit Through the Nutritious Garden to Supports the Adiwiyata School Program at Tamansiswa Middle School & Vocational School - Siti Rochmiyati; Didi Supriadi; Agustinus Eko Susetyo; Abdul Rahim (IMPACTS: International Journal of Empowerment and Community Services, 2023)
Purpose A comfortable and safe educational environment is necessary for learning. This service aims to develop the Tamansiswa spirit through nutritious gardens in support of the Adiwiyata school program at Tamansiswa Middle School & Vocational School Ngemplak Sleman. Methods – Empowerment and community service activities involving Tamansiswa Ngemplak Sleman Middle School & Vocational School students and Sarjanawiyata Tamansiswa University students. Result and discussions - Tamansiswa Ngemplak Sleman Middle School & Vocational School has some land that is still empty so it can be used as a nutritious garden planted with various fruits, vegetables and medicinal plants. In an effort to support the implementation of the Adiwiyata program at Tamansiswa Ngemplak Sleman Middle School & Vocational School, the UST Abdimas Team held a nutrition garden assistance activity for young Dewantara. Nutritious Gardens is a community-based program as an effort to fulfill the need for fruit, vegetables and medicines by utilizing school grounds and other media. Building awareness and advocacy for school residents in overcoming social problems such as health and the environment, introducing various types of fruit, vegetable and medicinal plants, Providing education on how to plant and care for plants, Utilizing empty yards to increase economic value. The result of the service activities carried out by the service team at Tamansiswa Ngemplak Sleman Middle School and Vocational School is that the school has a nutritious garden as a medium for activities to support the adiwiyata program. Teachers and students gain knowledge about the benefits, how to plant and how to maintain or care for plants, especially fruit plants, vegetables and medicinal plants. In the future, schools are expected to have added economic value from nutritious garden products. Conclusion – Community service activities for nutritious gardens in an effort to support the implementation of the Adiwiyata program can be carried out well. It is hoped that teachers and students will continue this activity so that they can gain knowledge about agriculture and added economic value.